[OP.5A.06] RENAL DENERVATION PREVENTS PROGRESSION OF HYPERTENSION AND CHANGES TO BAROREFLEX IN A RABBIT MODEL OF CHRONIC KIDNEY DISEASE. (September 2017) - Head, G.; Sata, Y.; Burke, S.; Denton, K.; Lambert, G.; Schlaich, M.
Abstract : Objective: We developed a rabbit model of moderate chronic kidney disease(CKD, induced by 11/12th nephrectomy which is characterised by rapid and sustained elevation of plasma creatinine and hypertension associated with elevation of renal sympathetic nerve activity (RSNA). Our aim was to determine the effects of renal denervation (RDN) on CKD-induced changes to mean arterial pressure (MAP), renal sympathetic nerve activity (RSNA), baroreflex function and renal function studied over a 4 week period. Design and method: Rabbits underwent RDN of the left renal nerve 2 weeks after CKD was induced by lesioning of the left kidney and right nephrectomy. In sham rabbits, both kidneys were denervated. MAP, RSNA recorded from the left renal nerve and baroreflexes were examined 2 and 4 weeks after RDN. Results: Two weeks after induction of CKD, creatinine increased by 59% and remained elevated by 41% over the following 4 weeks. MAP had increased by 14% to 77 ± 1 mmHg after CKD and continued to rise from this level by +8% and +13% after 2 and 4 weeks in sham RDN rabbits, while creatinine did not change. However, in rabbits which underwent RDN, there was no further increase in MAP (P<0.001 after 4 weeks RDN). RSNA was 23% lower 2–3 weeks following RDN than after sham RDN (P < 0.05) and the hypotensive response to pentolinium was also reduced by 50%. CKD shifted the RSNA baroreflex towards the higher MAP and this was reversed after 2 weeks of RDN with marked reductions in gain (38%) and range (42%). There was no further change to the baroreflex after 4 weeks RDN. Neither GFR (14 ± 2 ml/min in controls), which was 45% lower in CKD rabbits, nor creatinine levels were altered by 4 weeks of RDN. Conclusions: RDN is effective for 4 weeks in ameliorating the hypertension in this model of CKD. Sympathetic activation and changes to the RSNA baroreflex were also reversed without altering renal function. Our results suggest that RDN may be an effective treatment for moderate CKD.